Analisis Deskriptif Tentang Pandangan, Solusi, Dan Tipe Perundingan Konflik Berdasarkan Karakteristik Demografis Pada Kantor Kelurahan Hikun Kecamatan Tanjung Kabupaten Tabalong - Suryani, Lilis; Rahman, Aulia (stiatabalong.ac.id, 2025)
Conflict is an inevitable part of social and organizational life. In a work environment such as a village office, conflict can arise due to various factors, including differences in interests, ineffective communication, or differences in perception. In this context, the approach used to resolve conflict is greatly influenced by the characteristics of the individuals involved, such as age, gender, education level, and work experience. This is important to understand, especially in Hikun Village Tabalong Regency which has diverse demographic characteristics among its staff and the community it serves. This study aims to analyze the views, solutions, and types of negotiations used in resolving conflicts in Hikun Village based on the demographic characteristics of the local community. The research approach used is quantitative with a survey method. The number of research samples was 115 respondents with a non-probability sampling technique, namely convenience sampling. Data analysis used descriptive statistics through frequency tabulation and crosstabulation with the help of SPSS software. The results of the study showed that the dominant view of conflict based on demographic characteristics was interactional, the dominant conflict solution was compromise, and the dominant type of negotiation was integrative. This study shows that communities are more likely to use a cooperative approach in dealing with and resolving conflicts.